Good Governance (Tata Kelola) Dan Kualitas Pelayanan Kesehatan, Pengaruhnya Terhadap Kepuasaan Pasien, Di Rsud. Sogaten, Kota Madiun - Heni Churotul Aini (JURNAL SOSIAL, 2024)
Abstract— This research is motivated by limited efforts to build good governance in hospital management, so that it has not been able to produce quality health services that are easy, reasonable, affordable and high quality. With the increasingly complex demands of the community using hospital services in the form of comfort and convenience in health services, good governance is needed in the management of health service programs so that they can be presented in accordance with the hopes and desires of the community as health service patients. The presence of quality health services is very important to increase patient satisfaction, because with patient satisfaction the patient will use health services, but conversely if the patient feels dissatisfied they will switch to another hospital. The research method was carried out using a quantitative approach, and sampling was carried out by purposive sampling of 200 respondents from a total population of 400 respondents taken based on data on the average daily patient visits at RSUD. Sogaten, Madiun City. Data collection was carried out by observation, documentation and questionnaires. Meanwhile, data analysis was carried out through multiple linear regression with data processing through the SPSS program. The research results show that (1) there is an influence of Good Governance (Hospital Management) on Patient Satisfaction in RSUD. Sogaten, Madiun City. (2) there is an influence of the quality of health services on patient satisfaction with health services at RSUD. Sogaten, Madiun City. (3) there is an influence of Good Governance and Quality of Health Services on Patient Satisfaction with Health Services at RSUD. Sogaten, Madiun City. Good governance for public institutions is no exception to RSUD. Sogaten, Madiun, implementing the principles of good governance is not just an obligation but has become a necessity. There are 9 (nine) principles of good governance, namely: Participation, Rule of Law, Transparency, Responsiveness, Consensus Orientation, Effectiveness and Efficiency, Equity, Accountability, and Strategic Vision. The presence of good governance in hospital management will encourage improvements in the quality of health services, because all health personnel resources will be focused on carrying out their duties and obligations well, especially in the context of providing quality health services.